Pengaruh Kualitas Produk Dan Kualitas Layanan M Banking KB Star Terhadap Kepuasan Nasabah PT Bank KB Bukopin Tbk Cabang Bekasi - Yunike Ifani; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine whether there is an influence of product quality and service quality of M Banking KB Star on customer satisfaction at PT Bank KB Bukopin Tbk Bekasi Branch. This type of research is quantitative. The population in this study is 3.016. The sampling technique uses Non-Probability Sampling using Purposive Sampling techniques. The sample in this study amounted to 102 respondents. Data collection technique by distributing questionnaires via Google Form. Hypothesis testing in this research uses Multiple Linear Regression analysis. The research subjects were consumers of Bank KB Bukopin Tbk Bekasi Branch. The results of this research show that the product quality and service quality variables partially and simultaneously have a significant effect and have a positive influence on the consumer satisfaction variable.